2022
DOI: 10.1094/pdis-09-21-1875-re
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Almond (Prunus dulcis) Cultivars to Twig Canker and Shoot Blight Caused byDiaporthe amygdali

Abstract: Twenty-five almond cultivars were assessed for susceptibility to Diaporthe amygdali, causal agent of twig canker and shoot blight disease. In laboratory experiments, growing twigs were inoculated with four D. amygdali isolates. Moreover, growing shoots of almond cultivars grafted onto INRA ‘GF-677’ rootstock were used in four-year field inoculations with one D. amygdali isolate. In both type of experiments, inoculum consisted of agar plugs with mycelium, which were inserted underneath the bark and the lesion l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Fourteen accessions were evaluated as resistant and the highest level of resistance was identi ed in Malus sieboldii Rehder, which was effective against different isolates of the tested fungus 40 . Similar results were also found in pathogenicity studies using different fungal species and host plants [41][42][43][44][45][46] . The virulence of the tested fungal isolates as measured by lesion length was varied and this could be attributed to the genetic diversity among the isolates.…”
Section: Discussionsupporting
confidence: 86%
“…Fourteen accessions were evaluated as resistant and the highest level of resistance was identi ed in Malus sieboldii Rehder, which was effective against different isolates of the tested fungus 40 . Similar results were also found in pathogenicity studies using different fungal species and host plants [41][42][43][44][45][46] . The virulence of the tested fungal isolates as measured by lesion length was varied and this could be attributed to the genetic diversity among the isolates.…”
Section: Discussionsupporting
confidence: 86%
“…the Diatrypaceae E. lata; the Togniniaceae Phaeoacremonium amygdalinum and P. iranianum, confirmed by Raimondo et al (2021); and the Diaporthaceae Diaporthe amygdali, later confirmed by Varjas et al (2017), León et al (2020), andBeluzán et al (2022). Almond wood is also invaded by Pleurostoma richardsiae (Olmo et al, 2015) and Calosphaeria pulchella (Arzanlou et al, 2013).…”
Section: Fungal Trunk Diseases Of Nut Treesmentioning
confidence: 92%